Landasan Psikologis - Fina Sofiana; Hery Noer Aly (Departement of Mathematics Education, 2023)
The problem raised in this study is the Psychological Foundation of the Curriculum. In this study, the authors used the library research method, namely in writing articles, the authors used books as a source of data. Library research which is commonly called library research is carried out by examining written sources. The nature of this research is descriptive-analytic, discussed clearly, sequentially, and directed. The research subject in this article is from secondary data. Secondary sources, namely data obtained not from main books but from these books contain supporting data. Usually these books are the result of a review of the main book. The secondary sources used in this article come from books that discuss matters related to the curriculum development process. This paper focuses on the discussion of psychological aspects as a basis for developing the curriculum. Psychological foundation as part of the basic foundation in curriculum development has a strategic place in learning. However, curriculum development must be based on assumptions originating from psychology which include the study of what and how students develop, and how students learn.